PERANCANGAN SISTEM INFORMASI RAWAT JALAN PADA PUSKESMAS KELURAHAN JATIPADANG - Yuliana, Dyan; Hariyanto, Hariyanto; Lesmana, Sata (POLITEKNIK LP3I JAKARTA, 2018)
The Jatipadang Community Health Center (Puskesmas) is a government-owned agency, engaged in the health sector, located in Jatipadang Village, Pasar Minggu, South Jakarta. This health center requires an appropriate data processing system in order to create time efficiency and data accuracy that can support the operational, management and decision-making processes properly and accurately. The outpatient process at the Jatipadang Village Health Center does not yet use a computerized system. In the outpatient registration process, the officer must fill in the data manually, then the data is entered into the computer using Microsoft Excel software. Keywords: Information System, Outpatient, Puskesmas